استحداث تصميمات مستوحاة من الخداع البصري مقترحة لمعالجة العيوب الجسمية تصلح للفتاة الجامعية - محمد، أسماء علي أحمد Ahmed, Asma Ali; الخطيب، زينب عبدالحافظ علي (جامعة المنصورة - كلية التربية النوعية, 2014)
الحضارة الإسلامية هي إحدى البني الحضارية التي أثرت في تاريخ الإنسانية بكل أبعادها الدينية – التاريخية – الثقافية – الاقتصادية – العلمية وغيرها، وقد وضحت الأثار التي تركتها عن محصلة ما كان يدور بين رحاها خلال عمرها الزمني من أنشطة ذات مضامين فلسفية تنم عن بنية ذات خصوصية متميزة لها أصالتها وطاقتها الروحية بين الحضارات الإنسانية ومن هذه البني بنية الفنون البصرية، ومع بداية القرن العشرين شهد تاريخ الفنون بوجه عام ظهور سلسلة من الاتجاهات الفنية نتيجة التطور الفكري إلى جانب التقدم العلمي والتكنولوجي ومن أهم تلك الاتجاهات فن الخداع البصري (Optical Art) الذي يؤكد على العلاقة بين الفن والعلم لتحقيق رؤية فنية تتميز بالإبهار البصري وفق إحداثيات رياضية لعلم المنظور وعلم الضوء. وهو فن اعتمد فنانيه على النتائج العلمية الحديثة للتعبير عن الحركة بصورها المختلفة وذلك لمسايرة التقدم العلمي والتكنولوجي الذي ساد ذلك العصر لذا فقد اهتموا بنتائج نظرية الجشتالت وعلم الحركة وعلم البصريات وحققوا ذلك من خلال التباين اللوني وتباعد المسافات وتنظيم الخطوط والتصغير والتكبير وغيرها بحيث يوحي الشكل العام بالحركة مع أنه في الحقيقة ساكن. وأول من ابتدع فن الخداع البصري هو الفنان في العصر الإسلامي حيث أخذ هذا الفن طابع زخرفي هندسي متميز تحكم مفرداته قوانين رياضية وأسس هندسية تحقق عنها مجموعة من القيم الجمالية منها قيمة النظم الإيقاعية عن طريق سلسلة من العلاقات البسيطة أو المركبة كالتماس والتراكب والتضافر والتبادل والتي ينشأ عنها نظم (تصميمات) توحي بحركة تقديرية للعين هذه الحركة لها صفة الاستمرارية باستمرار الإدراك البصري لتلك التصميمات، ثم بعد ذلك بدأ هذا الاتجاه ينتشر بداية في مجال التصوير والنحت وعندما لقي قبولاً عن جمهور المشاهدين وقت ظهورها تم استغلالها في مجال الفنون التطبيقية من قبل المصممين الداخليين ومصممي الأزياء والمنسوجات ومصممي الإعلانات. ونظرا لتعدد أنماط أجسام السيدات وكذا العيوب الجسمانية لديهن تري الباحثاتان أنه إذا تم استغلال هذه الحركة في مجال تصميم الأزياء بشكل مدروس سينتج عنه أفكار جيدة تحمل قدر من الإبتكارية لإخفاء العيوب الجسمية (الطول والنحافة – السمنة – عيوب الاكتاف- قصر وطول الرقبة – البطن البارز - الوسط العريض)، ومن هذا المنطلق فقد قامت الباحثاتان بعمل عدد من التصميمات الفنية القائمة على نظام الخداع البصري وتطبيقها في زخرفة مجموعة من البلوزات التي تصلح للفتاة الجامعية بهدف إظهار الجسم بالشكل الذي يقربه من النسب التي تتفق والجمال.
Islamic civilization is one of the brown civilization that influenced the history of humanity in all its dimensions religious - historical - cultural - economic - and other scientific. The sacrificed monuments left by the outcome of what was going on between waged during the lifetime of activities with philosophical implications reflect the structure of the privacy of distinct originality and spiritual capacity between human civilizations and this brown structure of the visual arts. With the beginning of the twentieth century witnessed the history of art in general appearance series of artistic trends result intellectual development in addition to scientific and technological progress and the most important of these trends art optical illusion (Optical Art), which emphasizes the relationship between art and science to achieve artistic vision characterized Balabhar optic according to the coordinates of sport science perspective and optics. It is an art adopted artists on scientific findings of modem expression of the movement in its various forms so as to keep pace with scientific and technological progress that has prevailed that era so they took care outcomes theory Aljstalt kinetics and optics and achieved through the contrast color and spacing distances and organize fonts and zoom and zoom and other so suggests the general shape movement With that in fact residents. The first invented the art of optical illusion is the artist in the Islamic era where taking this art stamp decorative geometric privileged control vocabulary laws sports and foundations engineering achieved by a set of aesthetic values, including the value systems rhythmic through a series of relationships simple or complex Kaltmas and overlap and synergies, exchange and which give rise to systems (designs) suggest the discretion of the eye movement, this movement have constantly continuity status visual perception of these designs Then this trend began to spread early in the field of photography, sculpture and when he was accepted for the audience the time of its appearance has been exploited in the field of applied arts by interior designers and fashion designers, textile designers advertising. Given the multiple patterns objects ladies, as well as defects Gethsemane have Tri Albagesatan that if exploitation of this movement in the field of fashion design thoughtfully will result in good ideas bear much of the innovative to hide defects physical (height and thinness - Obesity - defects shoulders - Palace and along the neck - abdomen prominent. The vast center) In this sense, the Albagesatan the work of a number of artistic designs based system optical illusion And applied in the decoration of a set of jumpers that suitable for ph university in order to show the body shape that will bring him closer to rates that are consistent and beauty
Keywords: الفنون التشكيلية -- الخداع البصري -- الفن الإسلامي -- تصميم الأزياء